(untitled) - Noergaard, Tammy (Amsterdam, 2005)
This comprehensive textbook provides a broad and in-depth overview of embedded systems architecture for engineering students and embedded systems professionals. The book is well suited for undergraduate embedded systems courses in electronics/electrical engineering and engineering technology (EET) departments in universities and colleges, as well as for corporate training of employees
Keywords: Hệ thống máy tính kết hợp,Kiến trúc máy tính,Embedded computer systems,Computer architecture